1974
DOI: 10.1111/j.1600-0560.1974.tb00636.x
|View full text |Cite
|
Sign up to set email alerts
|

Pigmented Epidermal Cyst

Abstract: The pigmented epidermal cyst (black keratinous cyst) is peculiar to the Negro race. Ninety‐seven % of our cases occurred in Negroes. Thirty‐seven % of the epidermal cysts in Negroes were heavily pigmented. A relationship between the black keratinous cyst and hemochromatosis has been proposed. A change in the degree of pigmentation is more significant than the histologic demonstration of melanin pigment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Leyden et al (5) reported three pigmented epidermal cysts in a black patient with hemochromatosis and concluded that darkening in color of epidermal cysts may indicate the onset of hemochromatosis. Fieselman et al (4), however, disputed the relationship between pigmentation of the epidermal cysts and hemochromatosis, because 97% of epidermal cysts they studied were in blacks, and 37% of them were heavily pigmented; they concluded that the pigmented epidermal cyst is a normal variant in blacks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leyden et al (5) reported three pigmented epidermal cysts in a black patient with hemochromatosis and concluded that darkening in color of epidermal cysts may indicate the onset of hemochromatosis. Fieselman et al (4), however, disputed the relationship between pigmentation of the epidermal cysts and hemochromatosis, because 97% of epidermal cysts they studied were in blacks, and 37% of them were heavily pigmented; they concluded that the pigmented epidermal cyst is a normal variant in blacks.…”
Section: Discussionmentioning
confidence: 99%
“…The follicular cyst often shows a deeply pigmented appearance due to melanized hair shafts within the cavity (3). The pigmented epidermal cysts, peculiar variants of epidermal cysts (4), are black-brown or bluish in appearance.…”
Section: Introductionmentioning
confidence: 99%
“…To clarify, early publications considered pigmented follicular cysts to be follicular cysts with melanin pigment contained within the epithelium, 21 whereas most current usage of the term pertains to follicular cysts with pigmented hair shafts 22–24 . It is this latter convention that is used here.…”
Section: Cysts Of Follicular Differentiationmentioning
confidence: 99%
“…Among the morphologic variants, one of the less frequent is the pigmented epidermal cyst, which has been extensively documented in the literature. [1][2][3][4] Even these pigmented cysts do not pose any diagnostic challenges beyond being a morphologic rarity.…”
mentioning
confidence: 99%
“…However, the presence of melanin in cysts of individuals with high phototypes is not uncommon. 1,4 Prominent pigmentation of the cyst wall in individuals with low phototypes has only been reported on rare occasions. 4 When an epidermal cyst ruptures, it is common for extruded keratin to trigger a giant cell granulomatous foreign body response.…”
mentioning
confidence: 99%